MapReduce for data analytics - Roy Ananya. (2013)
The author’s final year project is a part of the Green Campus project which aims to conserve energy by using smart technologies. For developing smart technologies that conserve energy, historical data about energy resource usage has to be analysed by building mathematical models to uncover patterns and correlations and be able to predict abnormal energy usage.